DEVELOPING COMPUTER ENGINEERING AND INFORMATION TECHNOLOGY UNDERGRADUATES’ LEARNER AUTONOMY: INDIVIDUALISED INSTRUCTION IN ENGLISH CLASSROOM (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
The rapid development of information science and technology encourages lifelong learning and requires university graduates to be able to learn throughout their lives and have special abilities which help them search for continuous education and training opportunities. For students who associate their professional lives with computer sciences, learner autonomy is of immense importance since it helps them take full responsibility for success in professional life and career and contributes to the sustainable development of the current fast-moving digital society. As autonomous learners Computer Engineering and Information Technology undergraduates are able to define their goals clearly, to identify the most optimal learning strategies for achieving these goals and for acquiring new knowledge and skills necessary for their further professional development. The present study is aimed at finding out Computer Engineering and Information Technology undergraduates’ viewpoints on effectiveness of individualised instruction for developing their learner autonomy in English classroom. With this in mind, the team of researchers applied a questionnaire to a sample of Computer Engineering and Information Technology undergraduates who study at three higher education institutions of Ukraine. Data collection lasted for three months and took place in September-December 2022. The obtained results clearly demonstrate that individualised instruction delivered through online teaching tools and apps in English classroom enables university teachers to develop Computer Engineering and Information Technology Undergraduates’ learner autonomy effectively.